2016
DOI: 10.1111/ropr.12155
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Regulatory Agencies Punish? The Impact of Political Principals, Agency Culture, and Transaction Costs in Predicting Environmental Criminal Prosecution Outcomes in the United States

Abstract: Studies of administrative behavior are keen to examine the internal dynamics of agency decision making, as well the impact of external political actors on agency actions. Yet few studies apply these findings to the question of why agencies use their most punitive enforcement powers. Contrasting principal-agent, transaction costs, and organizational culture models of agency behavior, this study examines why regulatory agencies punish. Through content analysis of nearly one thousand of the U.S. Environmental Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…O'Hear's (2004) study looked at data on environmental prosecutions and found defendants in environmental crime prosecutions are often treated more leniently than defendants in other federal crime cases. Ozymy and Jarrell's (2016) study examined the predictors of federal environmental crime prosecution outcomes.…”
Section: Studying Green Crimementioning
confidence: 99%
See 3 more Smart Citations
“…O'Hear's (2004) study looked at data on environmental prosecutions and found defendants in environmental crime prosecutions are often treated more leniently than defendants in other federal crime cases. Ozymy and Jarrell's (2016) study examined the predictors of federal environmental crime prosecution outcomes.…”
Section: Studying Green Crimementioning
confidence: 99%
“…The number of criminal indictments pursued by the agency was only about 340 in 2007 (Jarrell and Ozymy, 2014). Large corporations and other environmental offenders understand the transaction costs associated with strong enforcement, which is why the deterrent value of environmental enforcement is often very low (Ozymy and Jarrell, 2016) and offenders may see enforcement as just another variable in the calculation of the economic cost of doing business.…”
Section: Studying Green Crimementioning
confidence: 99%
See 2 more Smart Citations
“…Even with all of these constraints, executive actors do manage to navigate the principal–agent game at the state and federal level to much success. Environmental policy is often studied as a classic case of difficult principal–agent dynamics related to a salient, but complex, policy area that gives agencies autonomy over policy creation and implementation within the political context of many actors competing to influence agency outcomes, including the agencies themselves (Ozymy & Jarrell, ). In this context we find Presidents Reagan, Clinton, and G.W.…”
mentioning
confidence: 99%